Importance of age at infection with HIV-1 for survival and development of AIDS in UK haemophilia population. UK Haemophilia Centre Directors' Organisation. - Darby, S; Ewart, D; Giangrande, P; Spooner, R; Rizza, C (1996)
BACKGROUND: Greater age at infection with HIV-1 is known to be associated with shorter time to development of AIDS, but the size of the differences between people infected in infancy and those infected in old age has not been examined in a single large population of patients with death as an endpoint. We, therefore, investigated the role of age at seroconversion in the entire UK population of haemophiliacs. METHODS: We studied 1216 HIV-1-infected haemophilia patients in the UK who were registered with the National Haemophilia Register and were alive on Jan 1, 1985. Their estimated ages at HIV-1 seroconversion ranged from 8 months to 79 years. FINDINGS: 10 years after seroconversion 67% (95% Cl 64-69) of the population were still alive. Survival was strongly related to age at seroconversion (86% [82-90], 72% [68-76], 45% [39-51], and 12% [5-21] at 10 years among those patients who seroconverted at ages < 15, 15-34, 35-54, and > or = 55). This steep age-gradient in survival was not explained by deaths expected in the absence of HIV infection or by confounding with other factors such as haemophilia type or severity. The age-gradient was steeper for survival (ie, time from HIV-1 infection to death) than for time to diagnosis of AIDS, partly because survival after an AIDS diagnosis was poorer in older patients, and there was also a substantial increase in mortality among HIV-infected patients who did not satisfy the formal AIDS definition and this increase was greater in older patients. INTERPRETATION: Age at infection with HIV-1 is a more important determinant of survival than has previously been appreciated. Age should, therefore, be considered in future studies of disease progression, and studies that compare people infected at different ages should provide insight into the biology of the immune response to HIV-1.